Profitabilitas, Ukuran Perusahaan, Umur Perusahaan, Kepemilikan Institusional dan Pengungkapan Sustainability Report - Madani, Ni Kadek Novita; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
Sustainability report is measurable report that published by company regarding the economic, social, and environmental impacts of the company’s activity. This study aims to find the effect of profitability, company size, company age, and institutional ownership on sustainability report disclosures. The populations were listed companies on Indonesia stock exchange in 2016-2019 and published sustainability report as a sample. The method of determining sample using purposive sampling technique which is resulted 21 companies with 77 observations. The data analysis technique using multiple linier regression analysis which results profitability have no significant effect on sustainability report disclosure, company size in negative significant effect on sustainability report, companyaage have positive significant effect on sustainability report, and institutional ownership have no significant effectaon the sustainability report disclosure. Keywords: Sustainability; Profitability; Size; Age; Institutional.